2020
DOI: 10.1002/brb3.1995
|View full text |Cite
|
Sign up to set email alerts
|

Leonurine, a potential drug for the treatment of cardiovascular system and central nervous system diseases

Abstract: Leonurus japonicus Houtt., a traditional Chinese herbal medicine, is often used as a gynecological medicine with the effect of promoting blood circulation, regulating menstruation, clearing heat, and detoxificating. As the most important alkaloid in L. japonicus, leonurine has a wide range of biological activities, such as antioxidation, anti‐inflammation, and anti‐apoptosis. Cardiovascular system and central nervous system diseases are arrogant killers that threaten human lives and health around the world, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Numerous in vivo and in vitro experimental studies have confirmed the antiplatelet activity of PBCRBSCMs and their interaction with antiplatelet drugs. PBCRBSCMs and their active ingredients and antiplatelet drugs are widely used in the clinical treatment of coronary heart diseases [ 73 , 74 ]. A study comprising 16,856 patients in 37 first-class tertiary hospitals in China showed that the frequency of combined use of Suxiao Jiuxin Pill and aspirin was as high as 50.77%.…”
Section: The Mechanisms Of Pbcrbscm Combined With Antiplatelet Drugs In Ischemic Heart Diseasementioning
confidence: 99%
“…Numerous in vivo and in vitro experimental studies have confirmed the antiplatelet activity of PBCRBSCMs and their interaction with antiplatelet drugs. PBCRBSCMs and their active ingredients and antiplatelet drugs are widely used in the clinical treatment of coronary heart diseases [ 73 , 74 ]. A study comprising 16,856 patients in 37 first-class tertiary hospitals in China showed that the frequency of combined use of Suxiao Jiuxin Pill and aspirin was as high as 50.77%.…”
Section: The Mechanisms Of Pbcrbscm Combined With Antiplatelet Drugs In Ischemic Heart Diseasementioning
confidence: 99%
“…Leonurine (LEO) is a special alkaloid, which is found in Chinese motherwort (Leonurus japonicus Houtt). Numerous studies have shown that LEO exerts multiple biologic effects, including protective effects on ischemic myocardium and brain, 10,11) antioxidative, 12) and anti-inflammatory. 13) Song et al reported that LEO has an anti-inflammatory effect by inhibiting the expression of the TLR4 pathway in mammary glands of mice mastitis model.…”
Section: Introductionmentioning
confidence: 99%
“…By modifying the structure of LEO, the shortcomings regarding the low bioavailability, weak transmembrane ability, and poor fat solubility of LEO have been solved [ 13 ]. Previous studies have shown that LEO has a protective effect on the cardiovascular system, such as providing protection against hypoxia-induced myocyte cell death and myocardial infarction, attenuating myocardial fibrosis and preventing atherosclerosis [ 14 ]. Importantly, LEO has been proven to have anti-inflammatory and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%